Teachers’ Use of Cloud-Based Learning Management Systems in Malaysian Secondary Schools - Ziden, Azidah Abu; Nagor, Aznan; Ifedayo, Adu Emmanuel (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This paper discussed the study of the factors that determine the behavioural intention (BI) of teachers utilisation of cloud-based learning management systems (LMS) in Malaysian secondary schools. A survey methodology was introduced in this inquiry using 322 participants from 18 secondary schools in the country. Also, this research employed a structured questionnaire consisting of 43 questions that addressed seven factors: performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), self-efficacy (SE), hedonic motivation (HM) and BI. The adoption of quantitative methodology was meant to allow the research to gather extensive numerical data to understand the problematic adoption of Google Classroom applications in Malaysian high schools. However, the data collected were analysed descriptively and inferentially. These research findings showed that there were relationships that existed between the independent variables and teachers’ BI towards the utilisation of cloud-based LMS in Malaysian secondary school settings. The results of this study are relevant from both academic and managerial perspectives, providing solutions for future research in educational technology.